All-Optical Detection of Neuronal Membrane Depolarization in Live Cells Using Colloidal Quantum Dots - Caglar, Mustafa; Pandya, Raj; Xiao, James; Foster, Sarah K.; Divitini, Giorgio; Chen, Richard Y. S.; Greenham, Neil C.; Franze, Kristian; Rao, Akshay; Keyser, Ulrich F. (Nano Letters, 2019)
Luminescent semiconductor quantum dots (QDs) have recently been suggested as novel probes for imaging and sensing cell membrane voltages. However, a key bottleneck for their development is a lack of techniques to assess QD responses to voltages generated in the aqueous electrolytic environments typical of biological systems. Even more generally, there have been relatively few efforts to assess the response of QDs to voltage changes in live cells. Here, we develop a platform for monitoring the photoluminescence (PL) response of QDs under AC and DC voltage changes within aqueous ionic environments. We evaluate both traditional CdSe/CdS and more biologically compatible InP/ZnS QDs at a range of ion concentrations to establish their PL/voltage characteristics on chip. Wide-field, few-particle PL measurements with neuronal cells show the QDs can be used to track local voltage changes with greater sensitivity (I"PL up to twice as large) than state-of-The-Art calcium imaging dyes, making them particularly appealing for tracking subthreshold events. Additional physiological observation studies showed that while CdSe/CdS dots have greater PL responses on membrane depolarization, their lower cytotoxicity makes InP/ZnS far more suitable for voltage sensing in living systems. Our results provide a methodology for the rational development of QD voltage sensors and highlight their potential for imaging changes in cell membrane voltage.
CRIS-Team Scopus Importer:2020-08-12
Keywords: electric field; live cell; photoluminescence; Quantum dots; voltage sensing

Atomic force microscopy and its contribution to understanding the development of the nervous system - Franze, Kristian (Current Opinion in Genetics & Development, 2011)
While our understanding of the influence of biochemical signaling on cell functioning is increasing rapidly, the consequences of mechanical signaling are currently poorly understood. However, cells of the nervous system respond to their mechanical environment; their mechanosensitivity has important implications for development and disease. Atomic force microscopy provides a powerful technique to investigate the mechanical interaction of cells with their environment with high resolution. This method can be used to obtain high-resolution surface topographies, stiffness maps, and apply well-defined forces to samples at different length scales. This review summarizes recent advances of atomic force microscopy, provides an overview about state-of-the-art measurements, and suggests directions for future applications to investigate the involvement of mechanics in the development of the nervous system. © 2011 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-08-12

Atomic force microscopy-based force measurements on animal cells and tissues - Gautier, Helene O. B.; Thompson, Amelia J.; Achouri, Sarra; Koser, David E.; Holtzmann, Kathrin; Moeendarbary, Emad; Franze, Kristian (Methods in Cell Biology, 2015)
During development, normal functioning, as well as in certain pathological conditions, cells are influenced not only by biochemical but also by mechanical signals. Over the past two decades, atomic force microscopy (AFM) has become one of the key tools to investigate the mechanical properties and interactions of biological samples. AFM studies have provided important insights into the role of mechanical signaling in different biological processes. In this chapter, we introduce different applications of AFM-based force measurements, from experimental setup and sample preparation to data acquisition and analysis, with a special focus on nervous system mechanics. Combined with other microscopy techniques, AFM is a powerful tool to reveal novel information about molecular, cell, and tissue mechanics.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Adhesion; AFM; Biomechanics; Elastic modulus; Elasticity; Scanning force microscopy; SFM; Stiffness

Auxetic nuclei in embryonic stem cells exiting pluripotency - Pagliara, Stefano; Franze, Kristian; Mcclain, Crystal R.; Wylde, Georgew.; Fisher, Cynthia L.; Franklin, Robin J. M.; Kabla, Alexandre J.; Keyser, Ulrich F.; Chalut, Kevin J. (Nature Materials, 2014)
Embryonic stem cells (ESCs) self-renew in a state of naïve pluripotency in which they are competent to generate all somatic cells. It has been hypothesized that, before irreversibly committing, ESCs pass through at least one metastable transition state. This transition would represent a gateway for differentiation and reprogramming of somatic cells. Here, we show that during the transition, the nuclei of ESCs are auxetic: they exhibit a cross-sectional expansion when stretched and a cross-sectional contraction when compressed, and their stiffness increases under compression. We also show that the auxetic phenotype of transition ESC nuclei is driven at least in part by global chromatin decondensation. Through the regulation of molecular turnover in the differentiating nucleus by external forces, auxeticity could be a key element in mechanotransduction. Our findings highlight the importance of nuclear structure in the regulation of differentiation and reprogramming. © 2014 Macmillan Publishers Limited.
CRIS-Team Scopus Importer:2020-08-12

Axons in the Chick Embryo Follow Soft Pathways Through Developing Somite Segments - Schaeffer, Julia; Weber, Isabell P.; Thompson, Amelia J.; Keynes, Roger J.; Franze, Kristian (Frontiers in Cell and Developmental Biology, 2022)
During patterning of the peripheral nervous system, motor axons grow sequentially out of the neural tube in a segmented fashion to ensure functional integration of the motor roots between the surrounding cartilage and bones of the developing vertebrae. This segmented outgrowth is regulated by the intrinsic properties of each segment (somite) adjacent to the neural tube, and in particular by chemical repulsive guidance cues expressed in the posterior half. Yet, knockout models for such repulsive cues still display initial segmentation of outgrowing motor axons, suggesting the existence of additional, yet unknown regulatory mechanisms of axon growth segmentation. As neuronal growth is not only regulated by chemical but also by mechanical signals, we here characterized the mechanical environment of outgrowing motor axons. Using atomic force microscopy-based indentation measurements on chick embryo somite strips, we identified stiffness gradients in each segment, which precedes motor axon growth. Axon growth was restricted to the anterior, softer tissue, which showed lower cell body densities than the repulsive stiffer posterior parts at later stages. As tissue stiffness is known to regulate axon growth during development, our results suggest that motor axons also respond to periodic stiffness gradients imposed by the intrinsic mechanical properties of somites.
CRIS-Team Scopus Importer:2022-08-05
Keywords: AFM; axon pathfinding; nervous system development; somite polarity; spinal motor axons; stiffness patterns; tissue stiffness

Brain tissue mechanics is governed by microscale relations of the tissue constituents - Sáez, P.; Borau, C.; Antonovaite, N.; Franze, Kristian (Biomaterials, 2023)
Local mechanical tissue properties are a critical regulator of cell function in the central nervous system (CNS) during development and disorder. However, we still don't fully understand how the mechanical properties of individual tissue constituents, such as cell nuclei or myelin, determine tissue mechanics. Here we developed a model predicting local tissue mechanics, which induces non-affine deformations of the tissue components. Using the mouse hippocampus and cerebellum as model systems, we show that considering individual tissue components alone, as identified by immunohistochemistry, is not sufficient to reproduce the local mechanical properties of CNS tissue. Our results suggest that brain tissue shows a universal response to applied forces that depends not only on the amount and stiffness of the individual tissue constituents but also on the way how they assemble. Our model may unify current incongruences between the mechanics of soft biological tissues and the underlying constituents and facilitate the design of better biomedical materials and engineered tissues. To this end, we provide a freely-available platform to predict local tissue elasticity upon providing immunohistochemistry images and stiffness values for the constituents of the tissue.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Brain mechanics; Inmunochemistry; Mechanobiology; Soft tissue mechanics; Tissue engineering

Brain tissue stiffness is a sensitive marker for acidosis - Holtzmann, Kathrin; Gautier, Helene O. B.; Christ, Andreas F.; Guck, Jochen; Karadottir, Ragnhildur Thora; Franze, Kristian (Journal of Neuroscience Methods, 2016)
Background Carbon dioxide overdose is frequently used to cull rodents for tissue harvesting. However, this treatment may lead to respiratory acidosis, which potentially could change the properties of the investigated tissue. New method Mechanical tissue properties often change in pathological conditions and may thus offer a sensitive generic readout for changes in biological tissues with clinical relevance. In this study, we performed force-indentation measurements with an atomic force microscope on acute cerebellar slices from adult rats to test if brain tissue undergoes changes following overexposure to CO2 compared to other methods of euthanasia. Results The pH significantly decreased in brain tissue of animals exposed to CO2. Concomitant with the drop in pH, cerebellar grey matter significantly stiffened. Tissue stiffening was reproduced by incubation of acute cerebellar slices in acidic medium. Comparison with existing methods Tissue stiffness provides an early, generic indicator for pathophysiological changes in the CNS. Atomic force microscopy offers unprecedented high spatial resolution to detect such changes. Conclusions Our results indicate that the stiffness particularly of grey matter strongly correlates with changes of the pH in the cerebellum. Furthermore, the method of tissue harvesting and preparation may not only change tissue stiffness but very likely also other physiologically relevant parameters, highlighting the importance of appropriate sample preparation.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Acidosis; AFM; Carbon dioxide; Cerebellum; Mechanical properties; Tissue mechanics

Cell surface fluctuations regulate early embryonic lineage sorting - Yanagida, Ayaka; Corujo-Simon, Elena; Revell, Christopher K.; Sahu, Preeti; Stirparo, Giuliano G.; Aspalter, Irene M.; Winkel, Alex K.; Peters, Ruby; De Belly, Henry; Cassani, Davide A. D.; Achouri, Sarra; Blumenfeld, Raphael; et al. (Cell, 2022)
In development, lineage segregation is coordinated in time and space. An important example is the mammalian inner cell mass, in which the primitive endoderm (PrE, founder of the yolk sac) physically segregates from the epiblast (EPI, founder of the fetus). While the molecular requirements have been well studied, the physical mechanisms determining spatial segregation between EPI and PrE remain elusive. Here, we investigate the mechanical basis of EPI and PrE sorting. We find that rather than the differences in static cell surface mechanical parameters as in classical sorting models, it is the differences in surface fluctuations that robustly ensure physical lineage sorting. These differential surface fluctuations systematically correlate with differential cellular fluidity, which we propose together constitute a non-equilibrium sorting mechanism for EPI and PrE lineages. By combining experiments and modeling, we identify cell surface dynamics as a key factor orchestrating the correct spatial segregation of the founder embryonic lineages.
CRIS-Team Scopus Importer:2022-08-05
Keywords: cell sorting; cell surface dynamics; cell surface mechanics; embryo development; lineage segregation; morphogenesis

CNS cell distribution and axon orientation determine local spinal cord mechanical properties - Koser, David E.; Moeendarbary, Emad; Hanne, Janina; Kuerten, Stefanie; Franze, Kristian (Biophysical Journal, 2015)
Mechanical signaling plays an important role in cell physiology and pathology. Many cell types, including neurons and glial cells, respond to the mechanical properties of their environment. Yet, for spinal cord tissue, data on tissue stiffness are sparse. To investigate the regional and direction-dependent mechanical properties of spinal cord tissue at a spatial resolution relevant to individual cells, we conducted atomic force microscopy (AFM) indentation and tensile measurements on acutely isolated mouse spinal cord tissue sectioned along the three major anatomical planes, and correlated local mechanical properties with the underlying cellular structures. Stiffness maps revealed that gray matter is significantly stiffer than white matter irrespective of directionality (transverse, coronal, and sagittal planes) and force direction (compression or tension) (Kg= ∼130 Pa vs. Kw= ∼70 Pa); both matters stiffened with increasing strain. When all data were pooled for each plane, gray matter behaved like an isotropic material under compression; however, subregions of the gray matter were rather heterogeneous and anisotropic. For example, in sagittal sections the dorsal horn was significantly stiffer than the ventral horn. In contrast, white matter behaved transversely isotropic, with the elastic stiffness along the craniocaudal (i.e., longitudinal) axis being lower than perpendicular to it. The stiffness distributions we found under compression strongly correlated with the orientation of axons, the areas of cell nuclei, and cellular in plane proximity. Based on these morphological parameters, we developed a phenomenological model to estimate local mechanical properties of central nervous system (CNS) tissue. Our study may thus ultimately help predicting local tissue stiffness, and hence cell behavior in response to mechanical signaling under physiological and pathological conditions, purely based on histological data.
CRIS-Team Scopus Importer:2020-08-12

Complex stiffness gradient substrates for studying mechanotactic cell migration - Kuo, Cheng-Hwa R.; Xian, Jian; Brenton, James D.; Franze, Kristian; Sivaniah, Easan (Advanced Materials, 2012)
Polyacrylamide gels are cast upon a stiff support with controlled topography, resulting in a thin gel layer of variable height. The topographical profiles project a stiffness map onto the gel, resulting in controlled linear and non-linear 2D stiffness gradients. Fibroblasts, which migrate towards stiffer substrates, accumulate in areas with a gel thickness below 15 μm. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-08-12
Keywords: atomic force microscopy; compliant substrates; durotaxis; stiffness gradients

Constriction imposed by basement membrane regulates developmental cell migration - López, Ester Molina; Kabanova, Anna; Winkel, Alexander; Franze, Kristian; Palacios, Isabel M.; Martín-Bermudo, María D. (Plos Biology, 2023)
The basement membrane (BM) is a specialized extracellular matrix (ECM), which underlies or encases developing tissues. Mechanical properties of encasing BMs have been shown to profoundly influence the shaping of associated tissues. Here, we use the migration of the border cells (BCs) of the Drosophila egg chamber to unravel a new role of encasing BMs in cell migration. BCs move between a group of cells, the nurse cells (NCs), that are enclosed by a monolayer of follicle cells (FCs), which is, in turn, surrounded by a BM, the follicle BM. We show that increasing or reducing the stiffness of the follicle BM, by altering laminins or type IV collagen levels, conversely affects BC migration speed and alters migration mode and dynamics. Follicle BM stiffness also controls pairwise NC and FC cortical tension. We propose that constraints imposed by the follicle BM influence NC and FC cortical tension, which, in turn, regulate BC migration. Encasing BMs emerge as key players in the regulation of collective cell migration during morphogenesis.
CRIS-Team Scopus Importer:2023-07-21

Contact inhibition controls cell survival and proliferation via YAP/TAZ-autophagy axis - Pavel, Mariana; Renna, Maurizio; Park, So Jung; Menzies, Fiona M.; Ricketts, Thomas; Fullgrabe, Jens; Ashkenazi, Avraham; Frake, Rebecca A.; Lombarte, Alejandro Carnicer; Bento, Carla F.; Franze, Kristian; Rubinsztein, David C. (Nature Communications, 2018)
Contact inhibition enables noncancerous cells to cease proliferation and growth when they contact each other. This characteristic is lost when cells undergo malignant transformation, leading to uncontrolled proliferation and solid tumor formation. Here we report that autophagy is compromised in contact-inhibited cells in 2D or 3D-soft extracellular matrix cultures. In such cells, YAP/TAZ fail to co-transcriptionally regulate the expression of myosin-II genes, resulting in the loss of F-actin stress fibers, which impairs autophagosome formation. The decreased proliferation resulting from contact inhibition is partly autophagy-dependent, as is their increased sensitivity to hypoxia and glucose starvation. These findings define how mechanically repressed YAP/TAZ activity impacts autophagy to contribute to core phenotypes resulting from high cell confluence that are lost in various cancers.
CRIS-Team Scopus Importer:2020-08-12

Cortical cell stiffness is independent of substrate mechanics - Rheinlaender, Johannes; Dimitracopoulos, Andrea; Wallmeyer, Bernhard; Kronenberg, Nils M.; Chalut, Kevin J.; Gather, Malte C.; Betz, Timo; Charras, Guillaume; Franze, Kristian (Nature Materials, 2020)
Cortical stiffness is an important cellular property that changes during migration, adhesion and growth. Previous atomic force microscopy (AFM) indentation measurements of cells cultured on deformable substrates have suggested that cells adapt their stiffness to that of their surroundings. Here we show that the force applied by AFM to a cell results in a significant deformation of the underlying substrate if this substrate is softer than the cell. This ‘soft substrate effect’ leads to an underestimation of a cell’s elastic modulus when analysing data using a standard Hertz model, as confirmed by finite element modelling and AFM measurements of calibrated polyacrylamide beads, microglial cells and fibroblasts. To account for this substrate deformation, we developed a ‘composite cell–substrate model’. Correcting for the substrate indentation revealed that cortical cell stiffness is largely independent of substrate mechanics, which has major implications for our interpretation of many physiological and pathological processes.
CRIS-Team Scopus Importer:2020-08-12

Defining the Adult Neural Stem Cell Niche Proteome Identifies Key Regulators of Adult Neurogenesis - Kjell, Jacob; Fischer-Sternjak, Judith; Thompson, Amelia J.; Friess, Christian; Sticco, Matthew J.; Salinas, Favio; Cox, Juergen; Martinelli, David C.; Ninkovic, Jovica; Franze, Kristian; Schiller, Herbert B.; Goetz, Magdalena (Cell Stem Cell, 2020)
The physical properties of stem cell niches are thought to mediate important regulatory functions. Here we provide a proteomic resource of the neural stem cell niche in comparison to gliogenic brain parenchyma, highlighting stiffness and the enzyme transglutaminase 2 as key regulators of neurogenesis.
CRIS-Team Scopus Importer:2020-08-12
Keywords: C1ql3; cerebral cortex; extracellular matrix; neuroblast; olfactory bulb; S100a6; subventricular zone; tissue stiffness; transglutaminase2; transit-amplifying progenitor

Development of the anterior-posterior axis is a self-organizing process in the absence of maternal cues in the mouse embryo - Bedzhov, Ivan; Bialecka, Monika; Zielinska, Agata; Kosalka, Joanna; Antonica, Francesco; Thompson, Amelia J.; Franze, Kristian; Zernicka-Goetz, Magdalena (Cell Research, 2015)
CRIS-Team Scopus Importer:2020-08-12

Differential tissue deformability underlies fluid pressure-driven shape divergence of the avian embryonic brain and spinal cord - McLaren, Susannah B.P.; Xue, Shi Lei; Ding, Siyuan; Winkel, Alexander K.; Baldwin, Oscar; Dwarakacherla, Shreya; Franze, Kristian; Hannezo, Edouard; Xiong, Fengzhu (Developmental Cell, 2025)
An enlarged brain underlies the complex central nervous system of vertebrates. The dramatic expansion of the brain that diverges its shape from the spinal cord follows neural tube closure during embryonic development. Here, we show that this differential deformation is encoded by a pre-pattern of tissue material properties in chicken embryos. Using magnetic droplets and atomic force microscopy, we demonstrate that the dorsal hindbrain is more fluid than the dorsal spinal cord, resulting in a thinning versus a resisting response to increasing lumen pressure, respectively. The dorsal hindbrain exhibits reduced apical actin and a disorganized laminin matrix consistent with tissue fluidization. Blocking the activity of neural-crest-associated matrix metalloproteinases inhibits hindbrain expansion. Transplanting dorsal hindbrain cells to the spinal cord can locally create an expanded brain-like morphology in some cases. Our findings raise questions in vertebrate head evolution and suggest a general role of mechanical pre-patterning in sculpting epithelial tubes.
CRIS-Team Scopus Importer:2025-05-23
Keywords: brain; development; ECM; extracellular matrix; lumen; morphogenesis; neural tube; pressure; spinal cord; tissue fluidity; tissue mechanics

Dual-beam laser traps in biology and medicine: When one beam is not enough - Whyte, Graeme; Lautenschlaeger, Franziska; Kreysing, Moritz; Boyde, Lars; Ekpenyong, Andrew; Delabre, Ulysse; Chalut, Kevin; Franze, Kristian; Guck, Jochen (Proceedings of SPIE - The International Society for Optical Engineering, 2010)
Optical traps are nowadays quite ubiquitous in biophysical and biological studies. The term is often used synonymously with optical tweezers, one particular incarnation of optical traps. However, there is another kind of optical trap consisting of two non-focused, counter-propagating laser beams. This dual-beam trap predates optical tweezers by almost two decades and currently experiences a renaissance. The advantages of dual-beam traps include lower intensities on the trapped object, decoupling from imaging optics, and the possibility to trap cells and cell clusters up to 100 microns in diameter. When used for deforming cells this trap is referred to as an optical stretcher. I will review several applications of such traps in biology and medicine for the detection of cancer cells, sorting stem cells, testing light guiding properties of retinal cells and the controlled rotation of cells for single cell tomography. © 2010 SPIE.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Cell mechanics; Optical cell rotator; Optical stretcher; Optical trap; Optical tweezers; Retina optics; Tomography

Dynamic traction force measurements of migrating immune cells in 3D biopolymer matrices - Böhringer, David; Cóndor, Mar; Bischof, Lars; Czerwinski, Tina; Gampl, Niklas; Ngo, Phuong; Bauer, Andreas; Bosch-Voskens, Caroline; Lopez Posadas, Rocío; Franze, Kristian; Budday, Silvia; Mark, Christoph; et al. (Nature Physics, 2024)
Immune cells, such as natural killer cells, migrate with high speeds of several micrometres per minute through dense tissue. However, the magnitude of the traction forces during this migration is unknown. Here we present a method to measure dynamic traction forces of fast migrating cells in biopolymer matrices from the observed matrix deformations. Our method accounts for the mechanical nonlinearity of the three-dimensional tissue matrix and can be applied to time series of confocal or bright-field image stacks. It allows for precise force reconstruction over a wide range of force magnitudes and object sizes—even when the imaged volume captures only a small part of the matrix deformation field. We demonstrate the broad applicability of our method by measuring forces from around 1 nN for axon growth cones up to around 10 μN for mouse intestinal organoids. We find that natural killer cells show bursts of large traction forces around 50 nN that increase with matrix stiffness. These force bursts are driven by myosin II contractility, mediated by integrin β1 adhesions, focal adhesion kinase and Rho-kinase activity, and occur predominantly when the cells migrate through narrow matrix pores.
CRIS-Team Scopus Importer:2024-11-29

ECM-Regulator timp Is Required for Stem Cell Niche Organization and Cyst Production in the Drosophila Ovary - Pearson, John R.; Zurita, Federico; Tomas-Gallardo, Laura; Diaz-Torres, Alfonsa; Del Carmen Diaz De La Loza, Maria; Franze, Kristian; Martin-Bermudo, Mara D.; Gonzalez-Reyes, Acaimo (PLoS Genetics, 2016)
The extracellular matrix (ECM) is a pivotal component adult tissues and of many tissue-specific stem cell niches. It provides structural support and regulates niche signaling during tissue maintenance and regeneration. In many tissues, ECM remodeling depends on the regulation of MMP (matrix metalloproteinase) activity by inhibitory TIMP (tissue inhibitors of metalloproteinases) proteins. Here, we report that the only Drosophila timp gene is required for maintaining the normal organization and function of the germline stem cell niche in adult females. timp mutant ovaries show reduced levels of both Drosophila Collagen IV α chains. In addition, tissue stiffness and the cellular organization of the ovarian niche are affected in timp mutants. Finally, loss of timp impairs the ability of the germline stem cell niche to generate new cysts. Our results demonstrating a crucial role for timp in tissue organization and gamete production thus provide a link between the regulation of ECM metabolism and tissue homeostasis.
CRIS-Team Scopus Importer:2020-08-12

Effective cell membrane tension is independent of polyacrylamide substrate stiffness - Kreysing, Eva; Hugh, Jeffrey Mc; Foster, Sarah K.; Andresen, Kurt; Greenhalgh, Ryan D.; Pillai, Eva K.; Dimitracopoulos, Andrea; Keyser, Ulrich F.; Franze, Kristian (PNAS Nexus, 2023)
The mechanical properties of the cellular environment may regulate many crucial cell functions. Membrane tension is thought to be a key player in the transduction of mechanical signals, such as substrate stiffness, into intracellular, biochemical responses. For example, it is widely accepted that the mechanosensitive ion channel, Piezo1, which is critical for many biological and biomedical processes, is activated by an increase in membrane tension. Investigating the effective membrane tension in living cells and how it relates to substrate stiffness and actomyosin-based contractility is important for a better understanding of the interactions between cell membrane and cortex, and it may help understand how mechanosensitive ion channels are activated.
CRIS-Team Scopus Importer:2023-12-15

Effect of vital dyes on human corneal endothelium and elasticity of Descemet’s membrane - Weber, Isabell P.; Rana, Mrinal; Thomas, Peter B. M.; Dimov, Ivan B.; Franze, Kristian; Rajan, Madhavan S. (PLoS ONE, 2017)
The purpose of this study was to evaluate the effects of vital dyes on human Descemet’s membranes (DMs) and endothelia. DMs of 25 human cadaveric corneas with research consent were treated with dyes routinely used in Descemet membrane endothelial keratoplasty (DMEK), 0.05% Trypan blue (TB) or a combination of 0.15% Trypan blue, 0.025% Brilliant blue and 4% Polyethylene glycol (commercial name Membrane Blue Dual; MB). The effects of these two dyes on (i) endothelial cell viability, (ii) DM mechanical properties as assessed by atomic force microscopy, and iii) qualitative DM dye retention were tested for two varying exposure times (one or four minutes). No significant differences in cell toxicity were observed between treatments with TB and MB at the two different exposure times (P = 0.21). Further, both dyes led to a significant increase in DM stiffness: exposure to TB and MB for one minute increased the apparent elastic modulus of the DM by 11.2% (P = 8*10−3) and 17.7%, respectively (P = 4*10−6). A four-minute exposure led to an increase of 8.6% for TB (P = 0.004) and 13.6% for MB (P = 0.03). Finally, at 25 minutes, the dye retention of the DM was considerably better for MB compared to TB. Taken together, a one-minute exposure to MB was found to improve DM visibility compared to TB, with a significant increase in DM stiffness and without detrimental effects on endothelial cell viability. The use of MB could therefore improve (i) visibility of the DM scroll, and (ii) intraoperative unfolding, enhancing the probability of successful DMEK surgery.
CRIS-Team Scopus Importer:2020-08-12

F-actin dynamics regulates mammalian organ growth and cell fate maintenance - Pocaterra, Arianna; Santinon, Giulia; Romani, Patrizia; Brian, Irene; Dimitracopoulos, Andrea; Ghisleni, Andrea; Carnicer-Lombarte, Alejandro; Forcato, Mattia; Braghetta, Paola; Montagner, Marco; Galuppini, Francesca; Aragona, Mariaceleste; et al. (Journal of Hepatology, 2019)
Background & Aims: In vitro, cell function can be potently regulated by the mechanical properties of cells and of their microenvironment. Cells measure these features by developing forces via their actomyosin cytoskeleton, and respond accordingly by regulating intracellular pathways, including the transcriptional coactivators YAP/TAZ. Whether mechanical cues are relevant for in vivo regulation of adult organ homeostasis, and whether this occurs through YAP/TAZ, remains largely unaddressed. Methods: We developed Capzb conditional knockout mice and obtained primary fibroblasts to characterize the role of CAPZ in vitro. In vivo functional analyses were carried out by inducing Capzb inactivation in adult hepatocytes, manipulating YAP/Hippo activity by hydrodynamic tail vein injections, and treating mice with the ROCK inhibitor, fasudil. Results: We found that the F-actin capping protein CAPZ restrains actomyosin contractility: Capzb inactivation alters stress fiber and focal adhesion dynamics leading to enhanced myosin activity, increased traction forces, and increased liver stiffness. In vitro, this rescues YAP from inhibition by a small cellular geometry; in vivo, it induces YAP activation in parallel to the Hippo pathway, causing extensive hepatocyte proliferation and leading to striking organ overgrowth. Moreover, Capzb is required for the maintenance of the differentiated hepatocyte state, for metabolic zonation, and for gluconeogenesis. In keeping with changes in tissue mechanics, inhibition of the contractility regulator ROCK, or deletion of the Yap1 mechanotransducer, reverse the phenotypes emerging in Capzb-null livers. Conclusions: These results indicate a previously unsuspected role for CAPZ in tuning the mechanical properties of cells and tissues, which is required in hepatocytes for the maintenance of the differentiated state and to regulate organ size. More generally, it indicates for the first time that mechanotransduction has a physiological role in maintaining liver homeostasis in mammals. Lay summary: The mechanical properties of cells and tissues (i.e. whether they are soft or stiff) are thought to be important regulators of cell behavior. Herein, we found that inactivation of the protein CAPZ alters the mechanical properties of cells and liver tissues, leading to YAP hyperactivation. In turn, this profoundly alters liver physiology, causing organ overgrowth, defects in liver cell differentiation and metabolism. These results reveal a previously uncharacterized role for mechanical signals in the maintenance of adult liver homeostasis.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Capping protein; CAPZ; F-actin dynamics; Gluconeogenesis; Glucose metabolism; Hepatocyte cell fate maintenance; Hippo; Liver homeostasis; Mechanotransduction; Organ growth; Xenobiotic metabolism; YAP

Force generation by molecular-motor-powered microtubule bundles; implications for neuronal polarization and growth - Jakobs, Maximilian; Franze, Kristian; Zemel, Assaf (Frontiers in Cellular Neuroscience, 2015)
The heavily cross-linked microtubule (MT) bundles found in neuronal processes play a central role in the initiation, growth and maturation of axons and dendrites; however, a quantitative understanding of their mechanical function is still lacking. We here developed computer simulations to investigate the dynamics of force generation in 1D bundles of MTs that are cross-linked and powered by molecular motors. The motion of filaments and the forces they exert are investigated as a function of the motor type (unipolar or bipolar), MT density and length, applied load, and motor connectivity. We demonstrate that only unipolar motors (e.g., kinesin-1) can provide the driving force for bundle expansion, while bipolar motors (e.g., kinesin-5) oppose it. The force generation capacity of the bundles is shown to depend sharply on the fraction of unipolar motors due to a percolation transition that must occur in the bundle. Scaling laws between bundle length, force, MT length and motor fraction are presented. In addition, we investigate the dynamics of growth in the presence of a constant influx of MTs. Beyond a short equilibration period, the bundles grow linearly in time. In this growth regime, the bundle extends as one mass forward with most filaments sliding with the growth velocity. The growth velocity is shown to be dictated by the inward flux of MTs, to inversely scale with the load and to be independent of the free velocity of the motors. These findings provide important molecular-level insights into the mechanical function of the MT cytoskeleton in normal axon growth and regeneration after injury.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Axon outgrowth; Force generation; Microtubules; Molecular motors; Neuronal polarization

Fumarate is an epigenetic modifier that elicits epithelial-to-mesenchymal transition - Sciacovelli, Marco; Goncalves, Emanuel; Johnson, Timothy Isaac; Zecchini, Vincent Roberto; Da Costa, Ana Sofia Henriques; Gaude, Edoardo; Drubbel, Alizee Vercauteren; Theobald, Sebastian Julian; Abbo, Sandra Riekje; Tran, Maxine Gia Binh; Rajeeve, Vinothini; Cardaci, Simone; et al. (Nature, 2016)
Mutations of the tricarboxylic acid cycle enzyme fumarate hydratase cause hereditary leiomyomatosis and renal cell cancer. Fumarate hydratase-deficient renal cancers are highly aggressive and metastasize even when small, leading to a very poor clinical outcome. Fumarate, a small molecule metabolite that accumulates in fumarate hydratase-deficient cells, plays a key role in cell transformation, making it a bona fide oncometabolite. Fumarate has been shown to inhibit α-ketoglutarate-dependent dioxygenases that are involved in DNA and histone demethylation. However, the link between fumarate accumulation, epigenetic changes, and tumorigenesis is unclear. Here we show that loss of fumarate hydratase and the subsequent accumulation of fumarate in mouse and human cells elicits an epithelial-to-mesenchymal-transition (EMT), a phenotypic switch associated with cancer initiation, invasion, and metastasis. We demonstrate that fumarate inhibits Tet-mediated demethylation of a regulatory region of the antimetastatic miRNA cluster mir-200ba429, leading to the expression of EMT-related transcription factors and enhanced migratory properties. These epigenetic and phenotypic changes are recapitulated by the incubation of fumarate hydratase-proficient cells with cell-permeable fumarate. Loss of fumarate hydratase is associated with suppression of miR-200 and the EMT signature in renal cancer and is associated with poor clinical outcome. These results imply that loss of fumarate hydratase and fumarate accumulation contribute to the aggressive features of fumarate hydratase-deficient tumours.
EVALuna2:34725

Growth cones as soft and weak force generators - Betz, Timo; Koch, Daniel; Lu, Yun-Bi; Franze, Kristian; Kaes, Josef A. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Many biochemical processes in the growth cone finally target its biomechanical properties, such as stiffness and force generation, and thus permit and control growth cone movement. Despite the immense progress in our understanding of biochemical processes regulating neuronal growth, growth cone biomechanics remains poorly understood. Here, we combine different experimental approaches to measure the structural and mechanical properties of a growth cone and to simultaneously determine its actin dynamics and traction force generation. Using fundamental physical relations, we exploited these measurements to determine the internal forces generated by the actin cytoskeleton in the lamellipodium. We found that, at timescales longer than the viscoelastic relaxation time of τ = 8.5 ± 0.5 sec, growth cones show liquid-like characteristics, whereas at shorter time scales they behaved elastically with a surprisingly low elastic modulus of E = 106 ± 21 Pa. Considering the growth cone's mechanical properties and retrograde actin flow, we determined the internal stress to be on the order of 30 pN per μm2. Traction force measurements confirmed these values. Hence, our results indicate that growth cones are particularly soft and weak structures that may be very sensitive to the mechanical properties of their environment.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Elasticity; Mechanics; Motility; Neuron; Scanning force microscopy

Integrating Chemistry and Mechanics: The Forces Driving Axon Growth - Franze, Kristian (Annual Reviews Inc., 2020)
The brain is our most complex organ. During development, neurons extend axons, which may grow over long distances along well-defined pathways to connect to distant targets. Our current understanding of axon pathfinding is largely based on chemical signaling by attractive and repulsive guidance cues. These cues instruct motile growth cones, the leading tips of growing axons, where to turn and where to stop. However, it is not chemical signals that cause motion-motion is driven by forces. Yet our current understanding of the mechanical regulation of axon growth is very limited. In this review, I discuss the origin of the cellular forces controlling axon growth and pathfinding, and how mechanical signals encountered by growing axons may be integrated with chemical signals. This mechanochemical cross talk is an important but often overlooked aspect of cell motility that has major implications for many physiological and pathological processes involving neuronal growth.
CRIS-Team Scopus Importer:2022-08-05
Keywords: forces; guidance; mechanosensitivity; mechanotransduction; neurons; pathfinding

Kein Irrtum der Natur: Wie Licht durch die umgekehrte Retina von Wirbeltieren gelangt - Agte, Silke; Francke, Mike; Franze, Kristian; Reichenbach, Andreas (Neuroforum, 2014)
In our eyes, as in the eyes of all vertebrates, images of the environment are projected onto an inverted retina where photons must pass through most of the retinal layers before they are captured by the light-sensitive cells. Light scattering in these retinal layers should decrease the signal-to-noise ratio of the images, and interfere with clear vision. Strikingly, however, our eye displays splendid visual abilities. This apparent contradiction could be resolved if intraretinal light scatter was minimized by the installation of optical elements facilitating light transmission through the tissue. Indeed, we have shown that one function of radial glial (Müller) cells is to act as effective optical fibers in the living retina, bypassing the light-scattering structures in front of the lightsensitive cells. Noteworthy, each Miiller cell serves as a 'private' light guide towards one individual cone photoreceptor cell, providing it with 'its' appropriate pixel of the environmental image.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Inverted retina; Light guidance; Müller glial cells; Tissue optics; Vision

Kymobutler, a deep learning software for automated kymograph analysis - Jakobs, Maximilian A. H.; Dimitracopoulos, Andrea; Franze, Kristian (eLife, 2019)
Kymographs are graphical representations of spatial position over time, which are often used in biology to visualise the motion of fluorescent particles, molecules, vesicles, or organelles moving along a predictable path. Although in kymographs tracks of individual particles are qualitatively easily distinguished, their automated quantitative analysis is much more challenging. Kymographs often exhibit low signal-to-noise-ratios (SNRs), and available tools that automate their analysis usually require manual supervision. Here we developed KymoButler, a Deep Learning-based software to automatically track dynamic processes in kymographs. We demonstrate that KymoButler performs as well as expert manual data analysis on kymographs with complex particle trajectories from a variety of different biological systems. The software was packaged in a web-based ‘one-click’ application for use by the wider scientific community (http://kymobutler.deepmirror.ai). Our approach significantly speeds up data analysis, avoids unconscious bias, and represents another step towards the widespread adaptation of Machine Learning techniques in biological data analysis.
CRIS-Team Scopus Importer:2020-08-12

Laminin Levels Regulate Tissue Migration and Anterior-Posterior Polarity during Egg Morphogenesis in Drosophila - Diaz De La Loza, Maria C.; Diaz-Torres, Alfonsa; Zurita, Federico; Rosales-Nieves, Alicia E.; Moeendarbary, Emad; Franze, Kristian; Martin-Bermudo, Maria D.; Gonzalez-Reyes, Acaimo (Cell Reports, 2017)
Basement membranes (BMs) are specialized extracellular matrices required for tissue organization and organ formation. We study the role of laminin and its integrin receptor in the regulation of tissue migration during Drosophila oogenesis. Egg production in Drosophila involves the collective migration of follicle cells (FCs) over the BM to shape the mature egg. We show that laminin content in the BM increases with time, whereas integrin amounts in FCs do not vary significantly. Manipulation of integrin and laminin levels reveals that a dynamic balance of integrin-laminin amounts determines the onset and speed of FC migration. Thus, the interplay of ligand-receptor levels regulates tissue migration in vivo. Laminin depletion also affects the ultrastructure and biophysical properties of the BM and results in anterior-posterior misorientation of developing follicles. Laminin emerges as a key player in the regulation of collective cell migration, tissue stiffness, and the organization of anterior-posterior polarity in Drosophila.
CRIS-Team Scopus Importer:2020-08-12
Keywords: anterior-posterior polarity; collective migration; Drosophila oogenesis; epithelial migration; integrin; laminin

Late Endosomes Act as mRNA Translation Platforms and Sustain Mitochondria in Axons - Cioni, Jean-Michel; Lin, Julie Qiaojin; Holtermann, Anne V.; Koppers, Max; Jakobs, Maximilian A. H.; Azizi, Afnan; Turner-Bridger, Benita; Shigeoka, Toshiaki; Franze, Kristian; Harris, William A.; Holt, Christine E. (Cell, 2019)
Local translation regulates the axonal proteome, playing an important role in neuronal wiring and axon maintenance. How axonal mRNAs are localized to specific subcellular sites for translation, however, is not understood. Here we report that RNA granules associate with endosomes along the axons of retinal ganglion cells. RNA-bearing Rab7a late endosomes also associate with ribosomes, and real-time translation imaging reveals that they are sites of local protein synthesis. We show that RNA-bearing late endosomes often pause on mitochondria and that mRNAs encoding proteins for mitochondrial function are translated on Rab7a endosomes. Disruption of Rab7a function with Rab7a mutants, including those associated with Charcot-Marie-Tooth type 2B neuropathy, markedly decreases axonal protein synthesis, impairs mitochondrial function, and compromises axonal viability. Our findings thus reveal that late endosomes interact with RNA granules, translation machinery, and mitochondria and suggest that they serve as sites for regulating the supply of nascent pro-survival proteins in axons.
CRIS-Team Scopus Importer:2020-08-12
Keywords: axon maintenance; Charcot-Marie-Tooth type 2B; endosome; local protein synthesis; lysosome; mitochondria; mRNA translation; retinal ganglion cell; RNA trafficking

Long-term imaging of cellular forces with high precision by elastic resonator interference stress microscopy - Kronenberg, Nils M.; Liehm, Philipp; Steude, Anja; Knipper, Johanna A.; Borger, Jessica G.; Scarcelli, Giuliano; Franze, Kristian; Powis, Simon J.; Gather, Malte C. (Nature Cell Biology, 2017)
Cellular forces are crucial for many biological processes but current methods to image them have limitations with respect to data analysis, resolution and throughput. Here, we present a robust approach to measure mechanical cell-substrate interactions in diverse biological systems by interferometrically detecting deformations of an elastic micro-cavity. Elastic resonator interference stress microscopy (ERISM) yields stress maps with exceptional precision and large dynamic range (2 nm displacement resolution over a >1 μm range, translating into 1 pN force sensitivity). This enables investigation of minute vertical stresses (<1 Pa) involved in podosome protrusion, protein-specific cell-substrate interaction and amoeboid migration through spatial confinement in real time. ERISM requires no zero-force reference and avoids phototoxic effects, which facilitates force monitoring over multiple days and at high frame rates and eliminates the need to detach cells after measurements. This allows observation of slow processes such as differentiation and further investigation of cells, for example, by immunostaining.
CRIS-Team Scopus Importer:2020-08-12

Measurement force, speed, and postmortem time affect the ratio of CNS gray-to-white-matter elasticity - Becker, Julia Monika; Winkel, Alexander Kevin; Kreysing, Eva; Franze, Kristian (Biophysical Journal, 2025)
For several decades, many attempts have been made to characterize the mechanical properties of gray and white matter, which constitute the two main compartments of the central nervous system, with various methods and contradictory results. In particular, the ratio of gray-to-white-matter elasticity is sometimes larger than 1 and sometimes smaller; the reason for this apparent discrepancy is currently unknown. Here, we exploited atomic force microscopy-based indentation measurements to systematically investigate how the measurement force, measurement speed, postmortem interval, and temperature affect the measured elasticity of spinal cord tissue and, in particular, the ratio of gray-to-white-matter elasticity (Kg/Kw). Within the explored parameter space, increasing measurement force and speed increased the measured elasticity of both gray and white matter. However, Kg/Kw declined from values as high as ∼5 at low forces and speeds to ∼1 for high forces and speeds. Kg/Kw also strongly depended on the anatomical plane in which the measurements were conducted and was considerably higher in transverse sections compared with longitudinal sections. Furthermore, the postmortem interval impacted both the absolute measured tissue elasticity and Kg/Kw. Gray matter elasticity started decreasing ∼3 h postmortem until reaching a plateau after ∼6 h. In contrast, white matter elasticity started declining from the beginning of the measurements until ∼6 h postmortem, when it also leveled off. As a result, Kg/Kw increased until ∼6 h postmortem before stabilizing. Between 20 and 38°C, both gray and white matter elasticity decreased at a similar rate without affecting Kg/Kw. We have thus identified differences in the response of gray and white matter to varying strains and strain rates, and the postmortem interval, and excluded temperature as a factor affecting Kg/Kw. These differential responses likely contribute to the contradictory results obtained with different methods working in different strain regimes.
CRIS-Team Scopus Importer:2025-04-18

Mechanical behavior of the hippocampus and corpus callosum: An attempt to reconcile ex vivo with in vivo and micro with macro properties - Bertalan, Gergerly; Becker, Julia; Tzschätzsch, Heiko; Morr, Anna; Herthum, Helge; Shahryari, Mehrgan; Greenhalgh, Ryan D.; Guo, Jing; Schröder, Leif; Alzheimer, Christian; Budday, Silvia; Franze, Kristian; et al. (Journal of the Mechanical Behavior of Biomedical Materials, 2023)
Mechanical properties of brain tissue are very complex and vary with the species, region, method, and dynamic range, and between in vivo and ex vivo measurements. To reconcile this variability, we investigated in vivo and ex vivo stiffness properties of two distinct regions in the human and mouse brain - the hippocampus (HP) and the corpus callosum (CC) - using different methods. Under quasi-static conditions, we examined ex vivo murine HP and CC by atomic force microscopy (AFM). Between 16 and 40Hz, we investigated the in vivo brains of healthy volunteers by magnetic resonance elastography (MRE) in a 3-T clinical scanner. At high-frequency stimulation between 1000 and 1400Hz, we investigated the murine HP and CC ex vivo and in vivo with MRE in a 7-T preclinical system. HP and CC showed pronounced stiffness dispersion, as reflected by a factor of 32–36 increase in shear modulus from AFM to low-frequency human MRE and a 25-fold higher shear wave velocity in murine MRE than in human MRE. At low frequencies, HP was softer than CC, in both ex vivo mouse specimens (p < 0.05) and in vivo human brains (p < 0.01) while, at high frequencies, CC was softer than HP under in vivo (p < 0.01) and ex vivo (p < 0.05) conditions. The standard linear solid model comprising three elements reproduced the observed HP and CC stiffness dispersions, while other two- and three-element models failed. Our results indicate a remarkable consistency of brain stiffness across species, ex vivo and in vivo states, and different measurement techniques when marked viscoelastic dispersion properties combining equilibrium and non-equilibrium mechanical elements are considered.
CRIS-Team Scopus Importer:2023-01-06
Keywords: AFM; Atomic force microscopy; Brain tissue; Corpus callosum; Hippocampus; MR elastography; MRE; Viscoelasticity; White matter

Mechanical difference between white and gray matter in the rat cerebellum measured by scanning force microscopy - Christ, Andreas F.; Franze, Kristian; Gautier, Helene; Moshayedi, Pouria; Fawcett, James; Franklin, Robin J. M.; Karadottir, Ragnhildur T.; Guck, Jochen (Journal of Biomechanics, 2010)
The mechanical properties of tissues are increasingly recognized as important cues for cell physiology and pathology. Nevertheless, there is a sparsity of quantitative, high-resolution data on mechanical properties of specific tissues. This is especially true for the central nervous system (CNS), which poses particular difficulties in terms of preparation and measurement. We have prepared thin slices of brain tissue suited for indentation measurements on the micrometer scale in a near-native state. Using a scanning force microscope with a spherical indenter of radius 20γm we have mapped the effective elastic modulus of rat cerebellum with a spatial resolution of 100γm. We found significant differences between white and gray matter, having effective elastic moduli of K=294±74 and 454±53Pa, respectively, at 3γm indentation depth (ng=245, nw=150 in four animals, p<0.05; errors are SD). In contrast to many other measurements on larger length scales, our results were constant for indentation depths of 2-4γm indicating a regime of linear effective elastic modulus. These data, assessed with a direct mechanical measurement, provide reliable high-resolution information and serve as a quantitative basis for further neuromechanical investigations on the mechanical properties of developing, adult and damaged CNS tissue. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Atomic force microscopy (AFM); Brain; Central nervous system (CNS); Elasticity; Stiffness

Mechanically compliant implants as a strategy to decrease foreign body reaction to nerve interfaces - Carnicer-Lombarte, Alejandro; Barone, Damiano G.; Malliaras, George G.; Fawcett, James; Franze, Kristian (Transactions of the Annual Meeting of the Society for Biomaterials and the Annual International Biomaterials Symposium, 2019)
Statement of Purpose: Neural interfaces are unique tools capable of establishing connections between the nervous systems and electronics; offering great potential in both clinic and basic research. Peripheral nerves are particularly attractive sites to position a neural interface, given the ease of access of these structures and the direct correlation between action potential transmission and activity at their target structure. Although many designs for peripheral nerve interfaces have been developed, they all face a major challenge upon chronic implantation: the foreign body reaction (FBR). This response, characterized by inflammation and fibrosis around the implanted body resulting in a build-up of a dense fibrotic capsule, occurs irrespective of the implanted material’s chemical properties. Implantable materials are, however, orders of magnitude stiffer than body tissues, which may tag them as foreign and trigger the foreign body response. In order to avoid this FBR, we have tested low-stiffness materials as potential components for neural interface manufacture. We prepared nerve implants coated with polyacrylamide hydrogels and silicone elastomers with very low mechanical stiffnesses, and evaluated the resulting FBR when chronically implanted in vivo.
CRIS-Team Scopus Importer:2020-08-12

Mechanical Regulation of Neurite Polarization and Growth: A Computational Study - Jakobs, Maximilian A. H.; Franze, Kristian; Zemel, Assaf (Biophysical Journal, 2020)
The densely packed microtubule (MT) array found in neuronal cell projections (neurites) serves two fundamental functions simultaneously: it provides a mechanically stable track for molecular motor-based transport and produces forces that drive neurite growth. The local pattern of MT polarity along the neurite shaft has been found to differ between axons and dendrites. In axons, the neurons’ dominating long projections, roughly 90% of the MTs orient with their rapidly growing plus end away from the cell body, whereas in vertebrate dendrites, their orientations are locally mixed. Molecular motors are known to be responsible for cytoskeletal ordering and force generation, but their collective function in the dense MT cytoskeleton of neurites remains elusive. We here hypothesized that both the polarity pattern of MTs along the neurite shaft and the shaft's global extension are simultaneously driven by molecular motor forces and should thus be regulated by the mechanical load acting on the MT array as a whole. To investigate this, we simulated cylindrical bundles of MTs that are cross-linked and powered by molecular motors by iteratively solving a set of force-balance equations. The bundles were subjected to a fixed load arising from actively generated tension in the actomyosin cortex enveloping the MTs. The magnitude of the load and the level of motor-induced connectivity between the MTs have been varied systematically. With an increasing load and decreasing motor-induced connectivity between MTs, the bundles became wider in cross section and extended more slowly, and the local MT orientational order was reduced. These results reveal two, to our knowledge, novel mechanical factors that may underlie the distinctive development of the MT cytoskeleton in axons and dendrites: the cross-linking level of MTs by motors and the load acting on this cytoskeleton during growth.
CRIS-Team Scopus Importer:2020-08-12

Mechanics in neuronal development and repair - Franze, Kristian; Janmey, Paul A.; Guck, Jochen (Annual Review of Biomedical Engineering, 2013)
Biological cells are well known to respond to a multitude of chemical signals. In the nervous system, chemical signaling has been shown to be crucially involved in development, normal functioning, and disorders of neurons and glial cells. However, there are an increasing number of studies showing that these cells also respond to mechanical cues. Here, we summarize current knowledge about the mechanical properties of nervous tissue and its building blocks, review recent progress in methodology and understanding of cellular mechanosensitivity in the nervous system, and provide an outlook on the implications of neuromechanics for future developments in biomedical engineering to aid overcoming some of the most devastating and currently incurable CNS pathologies such as spinal cord injuries and multiple sclerosis. Copyright © 2013 by Annual Reviews.
CRIS-Team Scopus Importer:2020-08-12
Keywords: brain; glial cells; mechanosensitivity; neurons; stiffness; viscoelasticity

Mechanics in the nervous system: From development to disease - Pillai, Eva K.; Franze, Kristian (Neuron, 2023)
Physical forces are ubiquitous in biological processes across scales and diverse contexts. This review highlights the significance of mechanical forces in nervous system development, homeostasis, and disease. We provide an overview of mechanical signals present in the nervous system and delve into mechanotransduction mechanisms translating these mechanical cues into biochemical signals. During development, mechanical cues regulate a plethora of processes, including cell proliferation, differentiation, migration, network formation, and cortex folding. Forces then continue exerting their influence on physiological processes, such as neuronal activity, glial cell function, and the interplay between these different cell types. Notably, changes in tissue mechanics manifest in neurodegenerative diseases and brain tumors, potentially offering new diagnostic and therapeutic target opportunities. Understanding the role of cellular forces and tissue mechanics in nervous system physiology and pathology adds a new facet to neurobiology, shedding new light on many processes that remain incompletely understood.<br
Keywords: neuronal mechanics; glia mechanics; brain mechanics; mechanobiology; mechanotransduction; forces; stiffness

Mechanochemical Crosstalk Produces Cell-Intrinsic Patterning of the Cortex to Orient the Mitotic Spindle. - Dimitracopoulos, Andrea; Srivastava, Pragya; Chaigne, Agathe; Win, Zaw; Shlomovitz, Roie; Lancaster, Oscar M.; Le Berre, Mael; Piel, Matthieu; Franze, Kristian; Salbreux, Guillaume; Baum, Buzz (Current Biology, 2020)
Proliferating animal cells are able to orient their mitotic spindles along their interphase cell axis, setting up the axis of cell division, despite rounding up as they enter mitosis. This has previously been attributed to molecular memory and, more specifically, to the maintenance of adhesions and retraction fibers in mitosis [1-6], which are thought to act as local cues that pattern cortical Gαi, LGN, and nuclear mitotic apparatus protein (NuMA) [3, 7-18]. This cortical machinery then recruits and activates Dynein motors, which pull on astral microtubules to position the mitotic spindle. Here, we reveal a dynamic two-way crosstalk between the spindle and cortical motor complexes that depends on a Ran-guanosine triphosphate (GTP) signal [12], which is sufficient to drive continuous monopolar spindle motion independently of adhesive cues in flattened human cells in culture. Building on previous work [1, 12, 19-23], we implemented a physical model of the system that recapitulates the observed spindle-cortex interactions. Strikingly, when this model was used to study spindle dynamics in cells entering mitosis, the chromatin-based signal was found to preferentially clear force generators from the short cell axis, so that cortical motors pulling on astral microtubules align bipolar spindles with the interphase long cell axis, without requiring a fixed cue or a physical memory of interphase shape. Thus, our analysis shows that the ability of chromatin to pattern the cortex during the process of mitotic rounding is sufficient to translate interphase shape into a cortical pattern that can be read by the spindle, which then guides the axis of cell division.
EVALuna2:473877

Mechanosensing is critical for axon growth in the developing brain - Koser, David E.; Thompson, Amelia J.; Foster, Sarah K.; Dwivedy, Asha; Pillai, Eva K.; Sheridan, Graham K.; Svoboda, Hanno; Viana, Matheus; Costa, Luciano Da F.; Guck, Jochen; Holt, Christine E.; Franze, Kristian (Nature Neuroscience, 2016)
During nervous system development, neurons extend axons along well-defined pathways. The current understanding of axon pathfinding is based mainly on chemical signaling. However, growing neurons interact not only chemically but also mechanically with their environment. Here we identify mechanical signals as important regulators of axon pathfinding. In vitro, substrate stiffness determined growth patterns of Xenopus retinal ganglion cell axons. In vivo atomic force microscopy revealed a noticeable pattern of stiffness gradients in the embryonic brain. Retinal ganglion cell axons grew toward softer tissue, which was reproduced in vitro in the absence of chemical gradients. To test the importance of mechanical signals for axon growth in vivo, we altered brain stiffness, blocked mechanotransduction pharmacologically and knocked down the mechanosensitive ion channel piezo1. All treatments resulted in aberrant axonal growth and pathfinding errors, suggesting that local tissue stiffness, read out by mechanosensitive ion channels, is critically involved in instructing neuronal growth in vivo.
CRIS-Team Scopus Importer:2020-08-12

Mechanosensitivity of astrocytes on optimized polyacrylamide gels analyzed by quantitative morphometry - Moshayedi, Pouria; Costa, Luciano Da F.; Christ, Andreas; Lacour, Stephanie P.; Fawcett, James; Guck, Jochen; Franze, Kristian (Journal of Physics: Condensed Matter, 2010)
Cells are able to detect and respond to mechanical cues from their environment. Previous studies have investigated this mechanosensitivity on various cell types, including neural cells such as astrocytes. In this study, we have carefully optimized polyacrylamide gels, commonly used as compliant growth substrates, considering their homogeneity in surface topography, mechanical properties, and coating density, and identified several potential pitfalls for the purpose of mechanosensitivity studies. The resulting astrocyte response to growth on substrates with shear storage moduli of G′ = 100 Pa and G′ = 10kPa was then evaluated as a function of coating density of poly-D-lysine using quantitative morphometric analysis. Astrocytes cultured on stiff substrates showed significantly increased perimeter, area, diameter, elongation, number of extremities and overall complexity if compared to those cultured on compliant substrates. A statistically significant difference in the overall morphological score was confirmed with an artificial intelligence-based shape analysis. The dependence of the cells' morphology on PDL coating density seemed to be weak compared to the effect of the substrate stiffness and was slightly biphasic, with a maximum at 10-100 νgml-1 PDL concentration. Our finding suggests that the compliance of the surrounding tissue in vivo may influence astrocyte morphology and behavior. © 2010 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2020-08-12

Metastable underwater superhydrophobicity - Poetes, Rosa; Holtzmann, Kathrin; Franze, Kristian; Steiner, Ullrich (Physical Review Letters, 2010)
Superhydrophobicity is generally considered to be a thermodynamically stable wetting state. The stability of the plastron (the thin air film separating the substrate from the water in the superhydrophobic state) was studied in underwater experiments. The plastron exhibited a rapid decay after a well defined onset time, which was found to be dependent on the immersion depth. The plastron decay is explained in terms of a model, which is based on confocal microscopy measurements. The limited underwater plastron stability explains the rarity of permanently submerged superhydrophobic surfaces in nature and limits their scope for commercial applications. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2020-08-12

Microglia mechanics: Immune activation alters traction forces and durotaxis - Bollmann, Lars; Koser, David E.; Shahapure, Rajesh; Gautier, Helene O. B.; Holzapfel, Gerhard A.; Scarcelli, Giuliano; Gather, Malte C.; Ulbricht, Elke; Franze, Kristian (Frontiers in Cellular Neuroscience, 2015)
Microglial cells are key players in the primary immune response of the central nervous system. They are highly active and motile cells that chemically and mechanically interact with their environment. While the impact of chemical signaling on microglia function has been studied in much detail, the current understanding of mechanical signaling is very limited. When cultured on compliant substrates, primary microglial cells adapted their spread area, morphology, and actin cytoskeleton to the stiffness of their environment. Traction force microscopy revealed that forces exerted by microglia increase with substrate stiffness until reaching a plateau at a shear modulus of 〜5 kPa. When cultured on substrates incorporating stiffness gradients, microglia preferentially migrated toward stiffer regions, a process termed durotaxis. Lipopolysaccharide-induced immune-activation of microglia led to changes in traction forces, increased migration velocities and an amplification of durotaxis. We finally developed a mathematical model connecting traction forces with the durotactic behavior of migrating microglial cells. Our results demonstrate that microglia are susceptible to mechanical signals, which could be important during central nervous system development and pathologies. Stiffness gradients in tissue surrounding neural implants such as electrodes, for example, could mechanically attract microglial cells, thus facilitating foreign body reactions detrimental to electrode functioning.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Biased random walk; CNS; Foreign body reaction; Gliosis; LPS; Mechanotaxis; Migration; Random walk

Müller glia provide essential tensile strength to the developing retina - Macdonald, Ryan B.; Randlett, Owen; Oswald, Julia; Yoshimatsu, Takeshi; Franze, Kristian; Harris, William A. (The Journal of Cell Biology, 2015)
To investigate the cellular basis of tissue integrity in a vertebrate central nervous system (CNS) tissue, we eliminated Müller glial cells (MG) from the zebrafish retina. For well over a century, glial cells have been ascribed a mechanical role in the support of neural tissues, yet this idea has not been specifically tested in vivo. We report here that retinas devoid of MG rip apart, a defect known as retinoschisis. Using atomic force microscopy, we show that retinas without MG have decreased resistance to tensile stress and are softer than controls. Laser ablation of MG processes showed that these cells are under tension in the tissue. Thus, we propose that MG act like springs that hold the neural retina together, finally confirming an active mechanical role of glial cells in the CNS.
CRIS-Team Scopus Importer:2020-08-12

Mutation of the ALS-/FTD-Associated RNA-Binding Protein FUS Affects Axonal Development. - van Tartwijk, Francesca W.; Wunderlich, Lucia C.S.; Mela, Ioanna; Makarchuk, Stanislaw; Jakobs, Maximilian A.H.; Qamar, Seema; Franze, Kristian; Kaminski Schierle, Gabriele S.; St George-Hyslop, Peter H.; Lin, Julie Qiaojin; Holt, Christine E.; Kaminski, Clemens F. (Journal of Neuroscience, 2024)
Aberrant condensation and localization of the RNA-binding protein (RBP) fused in sarcoma (FUS) occur in variants of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Changes in RBP function are commonly associated with changes in axonal cytoskeletal organization and branching in neurodevelopmental disorders. Here, we asked whether branching defects also occur in vivo in a model of FUS-associated disease. We use two reported Xenopus models of ALS/FTD (of either sex), the ALS-associated mutant FUS(P525L) and a mimic of hypomethylated FUS, FUS(16R). Both mutants strongly reduced axonal complexity in vivo. We also observed an axon looping defect for FUS(P525L) in the target area, which presumably arises due to errors in stop cue signaling. To assess whether the loss of axon complexity also had a cue-independent component, we assessed axonal cytoskeletal integrity in vitro. Using a novel combination of fluorescence and atomic force microscopy, we found that mutant FUS reduced actin density in the growth cone, altering its mechanical properties. Therefore, FUS mutants may induce defects during early axonal development.
EVALuna2:595175

Neurite branch retraction is caused by a threshold-dependent mechanical impact - Franze, Kristian; Gerdelmann, Jens; Weick, Michael; Betz, Timo; Pawlizak, Steve; Lakadamyali, Melike; Bayer, Johannes; Rillich, Katja; Goegler, Michael; Lu, Yun-Bi; Reichenbach, Andreas; Janmey, Paul; et al. (Biophysical Journal, 2009)
Recent results indicate that, in addition to chemical cues, mechanical stimuli may also impact neuronal growth. For instance, unlike most other cell types, neurons prefer soft substrates. However, the mechanisms responsible for the neuronal affinity for soft substrates have not yet been identified. In this study, we show that, in vitro, neurons continuously probe their mechanical environment. Growth cones visibly deform substrates with a compliance commensurate with their own. To understand the sensing of stiff substrates by growth cones, we investigated their precise temporal response to well-defined mechanical stress. When the applied stress exceeded a threshold of 274±41 pN/μm2, neurons retracted and re-extended their processes, thereby enabling exploration of alternative directions. A calcium influx through stretch-activated ion channels and the detachment of adhesion sites were prerequisites for this retraction. Our data illustrate how growing neurons may detect and avoid stiff substrates - as a mechanism involved in axonal branch pruning - and provide what we believe is novel support of the idea that mechanics may act as guidance cue for neuronal growth. © 2009 by the Biophysical Society.
CRIS-Team Scopus Importer:2020-08-12

Niche stiffness underlies the ageing of central nervous system progenitor cells - Segel, Michael; Neumann, Bjorn; Hill, Myfanwy F. E.; Weber, Isabell P.; Viscomi, Carlo; Zhao, Chao; Young, Adam; Agley, Chibeza C.; Thompson, Amelia J.; Gonzalez, Ginez A.; Sharma, Amar; Holmqvist, Staffan; et al. (Nature, 2019)
Ageing causes a decline in tissue regeneration owing to a loss of function of adult stem cell and progenitor cell populations1. One example is the deterioration of the regenerative capacity of the widespread and abundant population of central nervous system (CNS) multipotent stem cells known as oligodendrocyte progenitor cells (OPCs)2. A relatively overlooked potential source of this loss of function is the stem cell ‘niche’—a set of cell-extrinsic cues that include chemical and mechanical signals3,4. Here we show that the OPC microenvironment stiffens with age, and that this mechanical change is sufficient to cause age-related loss of function of OPCs. Using biological and synthetic scaffolds to mimic the stiffness of young brains, we find that isolated aged OPCs cultured on these scaffolds are molecularly and functionally rejuvenated. When we disrupt mechanical signalling, the proliferation and differentiation rates of OPCs are increased. We identify the mechanoresponsive ion channel PIEZO1 as a key mediator of OPC mechanical signalling. Inhibiting PIEZO1 overrides mechanical signals in vivo and allows OPCs to maintain activity in the ageing CNS. We also show that PIEZO1 is important in regulating cell number during CNS development. Thus we show that tissue stiffness is a crucial regulator of ageing in OPCs, and provide insights into how the function of adult stem and progenitor cells changes with age. Our findings could be important not only for the development of regenerative therapies, but also for understanding the ageing process itself.
CRIS-Team Scopus Importer:2020-08-12

Photomechanical responses in Drosophila photoreceptors - Hardie, Roger C.; Franze, Kristian (Science, 2012)
Phototransduction in Drosophila microvillar photoreceptor cells is mediated by a G protein-activated phospholipase C (PLC). PLC hydrolyzes the minor membrane lipid phosphatidylinositol 4,5-bisphosphate (PIP2), leading by an unknown mechanism to activation of the prototypical transient receptor potential (TRP) and TRP-like (TRPL) channels. We found that light exposure evoked rapid PLC-mediated contractions of the photoreceptor cells and modulated the activity of mechanosensitive channels introduced into photoreceptor cells. Furthermore, photoreceptor light responses were facilitated by membrane stretch and were inhibited by amphipaths, which alter lipid bilayer properties. These results indicate that, by cleaving PIP2, PLC generates rapid physical changes in the lipid bilayer that lead to contractions of the microvilli, and suggest that the resultant mechanical forces contribute to gating the light-sensitive channels.
CRIS-Team Scopus Importer:2020-08-12

Photonic crystal light collectors in fish retina improve vision in turbid water - Kreysing, Moritz; Pusch, Roland; Haverkate, Dorothee; Landsberger, Meik; Engelmann, Jacob; Ruiter, Janina; Mora-Ferrer, Carlos; Ulbricht, Elke; Grosche, Jens; Franze, Kristian; Streif, Stefan; Schumacher, Sarah; et al. (Science, 2012)
Despite their diversity, vertebrate retinae are specialized to maximize either photon catch or visual acuity. Here, we describe a functional type that is optimized for neither purpose. In the retina of the elephantnose fish (Gnathonemus petersii), cone photoreceptors are grouped together within reflecting, photonic crystal-lined cups acting as macroreceptors, but rod photoreceptors are positioned behind these reflectors. This unusual arrangement matches rod and cone sensitivity for detecting color-mixed stimuli, whereas the photoreceptor grouping renders the fish insensitive to spatial noise; together, this enables more reliable flight reactions in the fish's dim and turbid habitat as compared with fish lacking this retinal specialization.
CRIS-Team Scopus Importer:2020-08-12

Plakoglobin is a mechanoresponsive regulator of naive pluripotency - Kohler, Timo N.; De Jonghe, Joachim; Ellermann, Anna L.; Yanagida, Ayaka; Herger, Michael; Slatery, Erin M.; Weberling, Antonia; Munger, Clara; Fischer, Katrin; Mulas, Carla; Winkel, Alex; Ross, Connor; et al. (Nature Communications, 2023)
Biomechanical cues are instrumental in guiding embryonic development and cell differentiation. Understanding how these physical stimuli translate into transcriptional programs will provide insight into mechanisms underlying mammalian pre-implantation development. Here, we explore this type of regulation by exerting microenvironmental control over mouse embryonic stem cells. Microfluidic encapsulation of mouse embryonic stem cells in agarose microgels stabilizes the naive pluripotency network and specifically induces expression of Plakoglobin (Jup), a vertebrate homolog of β-catenin. Overexpression of Plakoglobin is sufficient to fully re-establish the naive pluripotency gene regulatory network under metastable pluripotency conditions, as confirmed by single-cell transcriptome profiling. Finally, we find that, in the epiblast, Plakoglobin was exclusively expressed at the blastocyst stage in human and mouse embryos – further strengthening the link between Plakoglobin and naive pluripotency in vivo. Our work reveals Plakoglobin as a mechanosensitive regulator of naive pluripotency and provides a paradigm to interrogate the effects of volumetric confinement on cell-fate transitions.
CRIS-Team Scopus Importer:2023-07-21

Prevention of the foreign body response to implantable medical devices by inflammasome inhibition - Barone, Damiano G.; Carnicer-Lombarte, Alejandro; Tourlomousis, Panagiotis; Hamilton, Russell S.; Prater, Malwina; Rutz, Alexandra L.; Dimov, Ivan B.; Malliaras, George G.; Lacour, Stephanie P.; Robertson, Avril A.B.; Franze, Kristian; Fawcett, James W.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
SignificanceImplantable electronic medical devices (IEMDs) are used for some clinical applications, representing an exciting prospect for the transformative treatment of intractable conditions such Parkinson's disease, deafness, and paralysis. The use of IEMDs is limited at the moment because, over time, a foreign body reaction (FBR) develops at the device-neural interface such that ultimately the IEMD fails and needs to be removed. Here, we show that macrophage nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activity drives the FBR in a nerve injury model yet integration of an NLRP3 inhibitor into the device prevents FBR while allowing full healing of damaged neural tissue to occur.
CRIS-Team Scopus Importer:2022-04-01
Keywords: foreign body reaction; MCC950; neural interfaces; NLRP3 inflammasome

Rapid changes in tissue mechanics regulate cell behaviour in the developing embryonic brain - Thompson, Amelia J.; Pillai, Eva K.; Dimov, Ivan B.; Foster, Sarah K.; Holt, Christine E.; Franze, Kristian (eLife, 2019)
Tissue mechanics is important for development; however, the spatio-temporal dynamics of in vivo tissue stiffness is still poorly understood. We here developed tiv-AFM, combining time-lapse in vivo atomic force microscopy with upright fluorescence imaging of embryonic tissue, to show that during development local tissue stiffness changes significantly within tens of minutes. Within this time frame, a stiffness gradient arose in the developing Xenopus brain, and retinal ganglion cell axons turned to follow this gradient. Changes in local tissue stiffness were largely governed by cell proliferation, as perturbation of mitosis diminished both the stiffness gradient and the caudal turn of axons found in control brains. Hence, we identified a close relationship between the dynamics of tissue mechanics and developmental processes, underpinning the importance of time-resolved stiffness measurements.
CRIS-Team Scopus Importer:2020-08-12
Keywords: atomic force microscopy; axon guidance; developmental biology; durotaxis; mechanics; mechanotransduction; physics of living systems; stiffness; xenopus

Regenerative capacity of neural tissue scales with changes in tissue mechanics post injury - Carnicer-Lombarte, Alejandro; Barone, Damiano G.; Wronowski, Filip; Malliaras, George G.; Fawcett, James W.; Franze, Kristian (Biomaterials, 2023)
Spinal cord injuries have devastating consequences for humans, as mammalian neurons of the central nervous system (CNS) cannot regenerate. In the peripheral nervous system (PNS), however, neurons may regenerate to restore lost function following injury. While mammalian CNS tissue softens after injury, how PNS tissue mechanics changes in response to mechanical trauma is currently poorly understood. Here we characterised mechanical rat nerve tissue properties before and after in vivo crush and transection injuries using atomic force microscopy-based indentation measurements. Unlike CNS tissue, PNS tissue significantly stiffened after both types of tissue damage. This nerve tissue stiffening strongly correlated with an increase in collagen I levels. Schwann cells, which crucially support PNS regeneration, became more motile and proliferative on stiffer substrates in vitro, suggesting that changes in tissue stiffness may play a key role in facilitating or impeding nervous system regeneration.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Crush injury; Nerve compartments; Nerve injury; Nerve stiffness; Schwann cells; Tissue mechanics

Retinal Glial (Müller) Cells: Sensing and responding to tissue stretch - Lindqvist, Niclas; Liu, Qing; Zajadacz, Joachim; Franze, Kristian; Reichenbach, Andreas (Investigative Ophthalmology & Visual Science, 2010)
Purpose. To test whether Müller glial cells sense, and respond to, mechanical tension in the retina. Methods. A device was designed to stretch the retina at right angles to its surface, across retinal layers. Pieces of retina were mounted between two hollow tubes, and uniaxial force was applied to the tissue using a micrometer-stepping motor. Müller cells were selectively stained with the fluorescent, calciumsensitive dye X-Rhod-1 and were monitored in real time during retinal stretch in vitro. Immunohistochemistry was used to study protein levels and activation of intracellular pathways in stretched retinas. Results. Müller cells responded acutely with transient increases in fluorescence during stretch, indicative of increased intracellular calcium levels. All the Müller cells elongated uniformly, and there was no apparent difference between retinal layers in resistance against mechanical deformation. After stretch, Müller cells showed fast activation of extracellular signal-regulated kinase (after 15 minutes), upregulation of transcription factor c-Fos (after 1 hour), and basic fibroblast growth factor (after 3 hours). No changes in intermediate filament protein expression were observed in Müller cells up to 3 hours after stretch. Conclusions. A novel technique was developed for real-time monitoring of Müller cells during retinal stretch, which allowed the identification of Müller cells as a mechanoresponsive cell type. Mechanical stress triggers molecular responses in Müller cells that could prevent retinal damage. © Association for Research in Vision and Ophthalmology.
CRIS-Team Scopus Importer:2020-08-12

Retinal regions shape human and murine Muller cell proteome profile and functionality - Kaplan, Lew; Drexler, Corinne; Pfaller, Anna M.; Brenna, Santra; Wunderlich, Kirsten A.; Dimitracopoulos, Andrea; Merl-Pham, Juliane; Perez, Maria-Theresa; Schlötzer-Schrehardt, Ursula; Enzmann, Volker; Samardzija, Marijana; Puig, Berta; et al. (Glia, 2022)
The human macula is a highly specialized retinal region with pit-like morphology and rich in cones. How Muller cells, the principal glial cell type in the retina, are adapted to this environment is still poorly understood. We compared proteomic data from cone- and rod-rich retinae from human and mice and identified different expression profiles of cone- and rod-associated Muller cells that converged on pathways representing extracellular matrix and cell adhesion. In particular, epiplakin (EPPK1), which is thought to play a role in intermediate filament organization, was highly expressed in macular Muller cells. Furthermore, EPPK1 knockout in a human Muller cell-derived cell line led to a decrease in traction forces as well as to changes in cell size, shape, and filopodia characteristics. We here identified EPPK1 as a central molecular player in the region-specific architecture of the human retina, which likely enables specific functions under the immense mechanical loads in vivo.
CRIS-Team WoS Importer:2022-11-25

Reversible switching between superhydrophobic states on a hierarchically structured surface - Verho, Tuukka; Korhonen, Juuso T.; Sainiemi, Lauri; Jokinen, Ville; Bower, Chris; Franze, Kristian; Franssila, Sami; Andrew, Piers; Ikkala, Olli; Ras, Robin H. A. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nature offers exciting examples for functional wetting properties based on superhydrophobicity, such as the self-cleaning surfaces on plant leaves and trapped air on immersed insect surfaces allowing underwater breathing. They inspire biomimetic approaches in science and technology. Superhydrophobicity relies on the Cassie wetting state where air is trapped within the surface topography. Pressure can trigger an irreversible transition from the Cassie state to the Wenzel state with no trapped air - this transition is usually detrimental for nonwetting functionality and is to be avoided. Here we present a new type of reversible, localized and instantaneous transition between two Cassie wetting states, enabled by two-level (dual-scale) topography of a superhydrophobic surface, that allows writing, erasing, rewriting and storing of optically displayed information in plastrons related to different length scales.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Bistable; Micropillars; Optical data storage; Silicone nanofilaments; Two-tier

Sensing the force in living embryos - Franze, Kristian (Nature Materials, 2024)
Spring-like force sensors bioprinted in the developing neural tube of growing chick embryos enable the measurement of forces generated by embryonic tissues with micrometre-level resolution.
CRIS-Team Scopus Importer:2024-11-08

Single-molecule analysis of endogenous β-actin mRNA trafficking reveals a mechanism for compartmentalized mRNA localization in axons - Turner-Bridger, Benita; Jakobs, Maximillian; Muresan, Leila; Wong, Hovy Ho-Wai; Franze, Kristian; Harris, William A.; Holt, Christine E. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
During embryonic nervous system assembly, mRNA localization is precisely regulated in growing axons, affording subcellular autonomy by allowing controlled protein expression in space and time. Different sets of mRNAs exhibit different localization patterns across the axon. However, little is known about how mRNAs move in axons or how these patterns are generated. Here, we couple molecular beacon technology with highly inclined and laminated optical sheet microscopy to image single molecules of identified endogenous mRNA in growing axons. By combining quantitative single-molecule imaging with biophysical motion models, we show that β-actin mRNA travels mainly as single copies and exhibits different motion-type frequencies in different axonal subcompartments. We find that β-actin mRNA density is fourfold enriched in the growth cone central domain compared with the axon shaft and that a modicum of directed transport is vital for delivery ofmRNA to the axon tip. Through mathematical modeling we further demonstrate that directional differences in motor-driven mRNA transport speeds are sufficient to generate β-actin mRNA enrichment at the growth cone. Our results provide insight into how mRNAs are trafficked in axons and a mechanism for generating different mRNA densities across axonal subcompartments.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Axon; Molecular beacon; RNA localization; Single molecule; β-actin

Soft Polydimethylsiloxane-Supported Lipid Bilayers for Studying T Cell Interactions. - Lippert, Anna H.; Dimov, Ivan B.; Winkel, Alexander K.; Humphrey, Jane; Mccoll, James; Chen, Kevin Y.; Santos, Ana M.; Jenkins, Edward; Franze, Kristian; Davis, Simon J.; Klenerman, David (Biophysical Journal, 2021)
Much of what we know about the early stages of T cell activation has been obtained from studies of T cells interacting with glass-supported lipid bilayers that favor imaging but are orders of magnitude stiffer than typical cells. We developed a method for attaching lipid bilayers to polydimethylsiloxane polymer supports, producing "soft bilayers" with physiological levels of mechanical resistance (Young's modulus of 4 kPa). Comparisons of T cell behavior on soft and glass-supported bilayers revealed that whereas late stages of T cell activation are thought to be substrate-stiffness dependent, early calcium signaling was unaffected by substrate rigidity, implying that early steps in T cell receptor triggering are not mechanosensitive. The exclusion of large receptor-type phosphatases was observed on the soft bilayers, however, even though it is yet to be demonstrated at authentic cell-cell contacts. This work sets the stage for an imaging-based exploration of receptor signaling under conditions closely mimicking physiological cell-cell contact.
EVALuna2:473876

Spatial heterogeneity of cell-matrix adhesive forces predicts human glioblastoma migration - Rezk, Rasha; Jia, Bill Zong; Wendler, Astrid; Dimov, Ivan; Watts, Colin; Markaki, Athina E.; Franze, Kristian; Kabla, Alexandre J. (2020)
Background: Glioblastoma (GBM) is a highly aggressive incurable brain tumor. The main cause of mortality in GBM patients is the invasive rim of cells migrating away from the main tumor mass and invading healthy parts of the brain. Although the motion is driven by forces, our current understanding of the physical factors involved in glioma infiltration remains limited. This study aims to investigate the adhesion properties within and between patients' tumors on a cellular level and test whether these properties correlate with cell migration. Methods: Six tissue samples were taken from spatially separated sections during 5-Aminolevulinic acid (5-ALA) fluorescence-guided surgery. Navigated biopsy samples were collected from strongly fluorescent tumor cores, a weak fluorescent tumor rim, and nonfluorescent tumor margins. A microfluidics device was built to induce controlled shear forces to detach cells from monolayer cultures. Cells were cultured on low modulus polydimethylsiloxane representative of the stiffness of brain tissue. Cell migration and morphology were then obtained using time-lapse microscopy. Results: GBM cell populations from different tumor fractions of the same patient exhibited different migratory and adhesive behaviors. These differences were associated with sampling location and amount of 5-ALA fluorescence. Cells derived from weak-and nonfluorescent tumor tissue were smaller, adhered less well, and migrated quicker than cells derived from strongly fluorescent tumor mass. Conclusions: GBM tumors are biomechanically heterogeneous. Selecting multiple populations and broad location sampling are therefore important to consider for drug testing.
CRIS-Team Scopus Importer:2022-08-05
Keywords: cell migration; cell-matrix adhesion; glioblastoma

Spatial mapping of the mechanical properties of the living retina using scanning force microscopy - Franze, Kristian; Francke, Mike; Guenter, Katrin; Christ, Andreas F.; Koerber, Nicole; Reichenbach, Andreas; Guck, Jochen (Soft Matter, 2011)
The retina is an active soft material, in which mechanosensitive cells are thought to respond to the local mechanical heterogeneity they encounter during development and adult physiological functioning. The retina is also constantly exposed to mechanical stress with shear and traction forces acting at its inner surface. Consequences of these forces depend on the tissue's resistance to deformation, which is characterized by its stiffness. However, currently there is a lack of high-resolution data on retinal mechanical properties. Here, we used scanning force microscopy to determine the apparent elastic modulus K of the retinal inner surface along the length of the eye with sub-millimetre resolution, and compared characteristic K values of the retinal quadrants. We found that the inner retina is a mechanically inhomogeneous tissue. Most elastic moduli were in the range of 940 to 1800 Pa; significant differences were found between areas less than 50 mm apart. To identify the origin of this mechanical inhomogeneity, we investigated the size and distribution of structures comprising the retinal surface: large cell bodies in the ganglion cell layer, nerve fibers, inner limiting membrane, and Müller cell endfeet. Our data suggest that the distribution of compliant nerve fiber bundles and stiff neuronal cell bodies contributes most to the mechanical properties of the inner retina. These data offer a basis for understanding cellular mechanoresistivity and -sensitivity in the retina as a mechanically active tissue, and they may help to understand mechanisms and consequences of a variety of retinopathological processes and their surgical treatment. © The Royal Society of Chemistry 2011.
CRIS-Team Scopus Importer:2020-08-12

Speed and sensitivity of phototransduction in Drosophila depend on degree of saturation of membrane phospholipids - Randall, Alex S.; Liu, Che-Hsiung; Chu, Brian; Zhang, Qifeng; Dongre, Sidharta A.; Juusola, Mikko; Franze, Kristian; Wakelam, Michael J. O.; Hardie, Roger C. (The Journal of Neuroscience, 2015)
Drosophila phototransduction is mediated via a G-protein-coupled PLC cascade. Recent evidence, including the demonstration that light evokes rapid contractions of the photoreceptors, suggested that the light-sensitive channels (TRP and TRPL) may be mechanically gated, together with protons released by PLC-mediated PIP2hydrolysis. If mechanical gating is involved we predicted that the response to light should be influenced by altering the physical properties of the membrane. To achieve this, we used diet to manipulate the degree of saturation of membrane phospholipids. In flies reared on a yeast diet, lacking polyunsaturated fatty acids (PUFAs), mass spectrometry showed that the proportion of polyunsaturated phospholipids was sevenfold reduced (from 38 to ∼5%) but rescued by adding a single species of PUFA (linolenic or linoleic acid) to the diet. Photoreceptors from yeast-reared flies showed a 2- to 3-fold increase in latency and time to peak of the light response, without affecting quantum bump waveform. In the absence of Ca2+ influx or in trp mutants expressing only TRPL channels, sensitivity to light was reduced up to ∼10-fold by the yeast diet, and essentially abolished in hypomorphic G-protein mutants (Gαq). PLC activity appeared little affected by the yeast diet; however, light-induced contractions measured by atomic force microscopy or the activation of ectopic mechanosensitive gramicidin channels were also slowed ∼2-fold. The results are consistent with mechanosensitive gating and provide a striking example of how dietary fatty acids can profoundly influence sensory performance in a classical G-protein-coupled signaling cascade.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Lipidomics; Mechanosensitivity; Phosphoinositide; Phospholipase C; Photoreceptors; PIP2

StemBond hydrogels control the mechanical microenvironment for pluripotent stem cells - Labouesse, Celine; Tan, Bao Xiu; Agley, Chibeza C.; Hofer, Moritz; Winkel, Alexander K.; Stirparo, Giuliano G.; Stuart, Hannah T.; Verstreken, Christophe M.; Mulas, Carla; Mansfield, William; Bertone, Paul; Franze, Kristian; et al. (Nature Communications, 2021)
Studies of mechanical signalling are typically performed by comparing cells cultured on soft and stiff hydrogel-based substrates. However, it is challenging to independently and robustly control both substrate stiffness and extracellular matrix tethering to substrates, making matrix tethering a potentially confounding variable in mechanical signalling investigations. Moreover, unstable matrix tethering can lead to poor cell attachment and weak engagement of cell adhesions. To address this, we developed StemBond hydrogels, a hydrogel in which matrix tethering is robust and can be varied independently of stiffness. We validate StemBond hydrogels by showing that they provide an optimal system for culturing mouse and human pluripotent stem cells. We further show how soft StemBond hydrogels modulate stem cell function, partly through stiffness-sensitive ERK signalling. Our findings underline how substrate mechanics impact mechanosensitive signalling pathways regulating self-renewal and differentiation, indicating that optimising the complete mechanical microenvironment will offer greater control over stem cell fate specification.
CRIS-Team Scopus Importer:2021-11-12

Tensed axons are on fire - Franze, Kristian (Proceedings of the National Academy of Sciences of the United States of America, 2024)
CRIS-Team Scopus Importer:2024-02-02

The biophysics of neuronal growth - Franze, Kristian; Guck, Jochen (Reports on Progress in Physics, 2010)
For a long time, neuroscience has focused on biochemical, molecular biological and electrophysiological aspects of neuronal physiology and pathology. However, there is a growing body of evidence indicating the importance of physical stimuli for neuronal growth and development. In this review we briefly summarize the historical background of neurobiophysics and give an overview over the current understanding of neuronal growth from a physics perspective. We show how biophysics has so far contributed to a better understanding of neuronal growth and discuss current inconsistencies. Finally, we speculate how biophysics may contribute to the successful treatment of lesions to the central nervous system, which have been considered incurable until very recently. © 2010 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2020-08-12

The Costs of Close Contacts: Visualizing the Energy Landscape of Cell Contacts at the Nanoscale - Kulenkampff, Klara; Lippert, Anna H.; Mccoll, James; Santos, Ana Mafalda; Ponjavic, Aleks; Jenkins, Edward; Humphrey, Jane; Winkel, Alexander; Franze, Kristian; Lee, Steven F.; Davis, Simon J.; Klenerman, David (Biophysical Journal, 2020)
Cell-cell contacts often underpin signaling between cells. For immunology, the binding of a T cell receptor to an antigen-presenting pMHC initiates downstream signaling and an immune response. Although this contact is mediated by proteins on both cells creating interfaces with gap sizes typically around 14 nm, many, often contradictory observations have been made regarding the influence of the contact on parameters such as the binding kinetics, spatial distribution, and diffusion of signaling proteins within the contact. Understanding the basic physical constraints on probes inside this crowded environment will help inform studies on binding kinetics and dynamics of signaling of relevant proteins in the synapse. By tracking quantum dots of different dimensions for extended periods of time, we have shown that it is possible to obtain the probability of a molecule entering the contact, the change in its diffusion upon entry, and the impact of spatial heterogeneity of adhesion protein density in the contact. By analyzing the contacts formed by a T cell interacting with adhesion proteins anchored to a supported lipid bilayer, we find that probes are excluded from contact entry in a size-dependent manner for gap-to-probe differences of 4.1 nm. We also observed probes being trapped inside the contact and a decrease in diffusion of up to 85% in dense adhesion protein contacts. This approach provides new, to our knowledge, insights into the nature of cell-cell contacts, revealing that cell contacts are highly heterogeneous because of topography- and protein-density-related processes. These effects are likely to profoundly influence signaling between cells.
CRIS-Team Scopus Importer:2020-08-12

The mechanical control of nervous system development - Franze, Kristian (Development, 2013)
The development of the nervous system has so far, to a large extent, been considered in the context of biochemistry, molecular biology and genetics. However, there is growing evidence that many biological systems also integrate mechanical information when making decisions during differentiation, growth, proliferation, migration and general function. Based on recent findings, I hypothesize that several steps during nervous system development, including neural progenitor cell differentiation, neuronal migration, axon extension and the folding of the brain, rely on or are even driven by mechanical cues and forces. © 2013. Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Brain folding; Force; Mechanics; Mechanosensitivity; Mechanotaxis; Mechanotransduction; Stiffness; Tension

The mechanical regulation of Eph/ephrin signaling in the developing brain - Sipkova, Jana; Mukherjee, Sudipta; Franze, Kristian (Biophysical Journal, 2023)
CRIS-Team Scopus Importer:2023-02-24

Theory for Durotactic Axon Guidance - Oliveri, Hadrien; Franze, Kristian; Goriely, Alain (Physical Review Letters, 2021)
During the development of the nervous system, neurons extend bundles of axons that grow and meet other neurons to form the neuronal network. Robust guidance mechanisms are needed for these bundles to migrate and reach their functional target. Directional information depends on external cues such as chemical or mechanical gradients. Unlike chemotaxis that has been extensively studied, the role and mechanism of durotaxis, the directed response to variations in substrate rigidity, remain unclear. We model bundle migration and guidance by rigidity gradients by using the theory of morphoelastic rods. We show that, at a rigidity interface, the motion of axon bundles follows a simple behavior analogous to optic ray theory and obeys Snell's law for refraction and reflection. We use this powerful analogy to demonstrate that axons can be guided by the equivalent of optical lenses and fibers created by regions of different stiffnesses.
CRIS-Team Scopus Importer:2021-04-09

The relationship between glial cell mechanosensitivity and foreign body reactions in the central nervous system - Moshayedi, Pouria; Ng, Gilbert; Kwok, Jessica C. F.; Yeo, Giles S. H.; Bryant, Clare E.; Fawcett, James W.; Franze, Kristian; Guck, Jochen (Biomaterials, 2014)
Devices implanted into the body become encapsulated due to a foreign body reaction. In the central nervous system (CNS), this can lead to loss of functionality in electrodes used to treat disorders. Around CNS implants, glial cells are activated, undergo gliosis and ultimately encapsulate the electrodes. The primary cause of this reaction is unknown. Here we show that the mechanical mismatch between nervous tissue and electrodes activates glial cells. Both primary rat microglial cells and astrocytes responded to increasing the contact stiffness from physiological values (. G' 100Pa) to shear moduli G'≥10kPa by changes in morphology and upregulation of inflammatory genes and proteins. Upon implantation of composite foreign bodies into rat brains, foreign body reactions were significantly enhanced around their stiff portions invivo. Our results indicate that CNS glial cells respond to mechanical cues, and suggest that adapting the surface stiffness of neural implants to that of nervous tissue could minimize adverse reactions and improve biocompatibility. © 2014 The Authors.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Astrocyte; FBR; Gliosis; Implant; Microglia; Stiffness

The role of cell body density in ruminant retina mechanics assessed by atomic force and Brillouin microscopy - Weber, Isabell P.; Yun, Seok Hyun; Scarcelli, Giuliano; Franze, Kristian (Physical Biology, 2017)
Cells in the central nervous system (CNS) respond to the stiffness of their environment. CNS tissue is mechanically highly heterogeneous, thus providing motile cells with region-specific mechanical signals. While CNS mechanics has been measured with a variety of techniques, reported values of tissue stiffness vary greatly, and the morphological structures underlying spatial changes in tissue stiffness remain poorly understood. We here exploited two complementary techniques, contact-based atomic force microscopy and contact-free Brillouin microscopy, to determine the mechanical properties of ruminant retinae, which are built up by different tissue layers. As in all vertebrate retinae, layers of high cell body densities ('nuclear layers') alternate with layers of low cell body densities ('plexiform layers'). Different tissue layers varied significantly in their mechanical properties, with the photoreceptor layer being the stiffest region of the retina, and the inner plexiform layer belonging to the softest regions. As both techniques yielded similar results, our measurements allowed us to calibrate the Brillouin microscopy measurements and convert the Brillouin shift into a quantitative assessment of elastic tissue stiffness with optical resolution. Similar as in the mouse spinal cord and the developing Xenopus brain, we found a strong correlation between nuclear densities and tissue stiffness. Hence, the cellular composition of retinae appears to strongly contribute to local tissue stiffness, and Brillouin microscopy shows a great potential for the application in vivo to measure the mechanical properties of transparent tissues.
CRIS-Team Scopus Importer:2020-08-12
Keywords: AFM; elastic modulus; stiffness; tissue mechanics; Young's modulus

The soft mechanical signature of glial scars in the central nervous system - Moeendarbary, Emad; Weber, Isabell P.; Sheridan, Graham K.; Koser, David E.; Soleman, Sara; Haenzi, Barbara; Bradbury, Elizabeth J.; Fawcett, James; Franze, Kristian (Nature Communications, 2017)
Injury to the central nervous system (CNS) alters the molecular and cellular composition of neural tissue and leads to glial scarring, which inhibits the regrowth of damaged axons. Mammalian glial scars supposedly form a chemical and mechanical barrier to neuronal regeneration. While tremendous effort has been devoted to identifying molecular characteristics of the scar, very little is known about its mechanical properties. Here we characterize spatiotemporal changes of the elastic stiffness of the injured rat neocortex and spinal cord at 1.5 and three weeks post-injury using atomic force microscopy. In contrast to scars in other mammalian tissues, CNS tissue significantly softens after injury. Expression levels of glial intermediate filaments (GFAP, vimentin) and extracellular matrix components (laminin, collagen IV) correlate with tissue softening. As tissue stiffness is a regulator of neuronal growth, our results may help to understand why mammalian neurons do not regenerate after injury.
CRIS-Team Scopus Importer:2020-08-12

Tissue stiffening coordinates morphogenesis by triggering collective cell migration in vivo - Barriga, Elias H.; Franze, Kristian; Charras, Guillaume; Mayor, Roberto (Nature, 2018)
Collective cell migration is essential for morphogenesis, tissue remodelling and cancer invasion. In vivo, groups of cells move in an orchestrated way through tissues. This movement involves mechanical as well as molecular interactions between cells and their environment. While the role of molecular signals in collective cell migration is comparatively well understood, how tissue mechanics influence collective cell migration in vivo remains unknown. Here we investigated the importance of mechanical cues in the collective migration of the Xenopus laevis neural crest cells, an embryonic cell population whose migratory behaviour has been likened to cancer invasion. We found that, during morphogenesis, the head mesoderm underlying the cephalic neural crest stiffens. This stiffening initiates an epithelial-to-mesenchymal transition in neural crest cells and triggers their collective migration. To detect changes in their mechanical environment, neural crest cells use mechanosensation mediated by the integrin-vinculin-talin complex. By performing mechanical and molecular manipulations, we show that mesoderm stiffening is necessary and sufficient to trigger neural crest migration. Finally, we demonstrate that convergent extension of the mesoderm, which starts during gastrulation, leads to increased mesoderm stiffness by increasing the cell density underneath the neural crest. These results show that convergent extension of the mesoderm has a role as a mechanical coordinator of morphogenesis, and reveal a link between two apparently unconnected processes - gastrulation and neural crest migration - via changes in tissue mechanics. Overall, we demonstrate that changes in substrate stiffness can trigger collective cell migration by promoting epithelial-to-mesenchymal transition in vivo. More broadly, our results raise the idea that tissue mechanics combines with molecular effectors to coordinate morphogenesis.
CRIS-Team Scopus Importer:2020-08-12

Tissue stiffness at the human maternal-fetal interface - Abbas, Yassen; Carnicer-Lombarte, Alejandro; Gardner, Lucy; Thomas, Jake; Brosens, Jan J.; Moffett, Ashley; Sharkey, Andrew M.; Franze, Kristian; Burton, Graham J.; Oyen, Michelle L. (Human Reproduction, 2019)
STUDY QUESTION: What is the stiffness (elastic modulus) of human nonpregnant secretory phase endometrium, first trimester decidua, and placenta? SUMMARY ANSWER: The stiffness of decidua basalis, the site of placental invasion, was an order of magnitude higher at 103 Pa compared to 102 Pa for decidua parietalis, nonpregnant endometrium and placenta. WHAT IS KNOWN ALREADY: Mechanical forces have profound effects on cell behavior, regulating both cell differentiation and migration. Despite their importance, very little is known about their effects on blastocyst implantation and trophoblast migration during placental development because of the lack of mechanical characterization at the human maternal-fetal interface. STUDY DESIGN, SIZE, DURATION: An observational study was conducted to measure the stiffness of ex vivo samples of human nonpregnant secretory endometrium (N = 5) and first trimester decidua basalis (N = 6), decidua parietalis (N = 5), and placenta (N = 5). The stiffness of the artificial extracellular matrix (ECM), Matrigel®, commonly used to study migration of extravillous trophoblast (EVT) in three dimensions and to culture endometrial and placental organoids, was also determined (N = 5). PARTICIPANTS/MATERIALS, SETTING, METHODS: Atomic force microscopy was used to perform ex vivo direct measurements to determine the stiffness of fresh tissue samples. Decidua was stained by immunohistochemistry (IHC) for HLA-G+ EVT to confirm whether samples were decidua basalis or decidua parietalis. Endometrium was stained with hematoxylin and eosin to confirm the presence of luminal epithelium. Single-cell RNA sequencing data were analyzed to determine expression of ECM transcripts by decidual and placental cells. Fibrillin 1, a protein identified by these data, was stained by IHC in decidua basalis. MAIN RESULTS AND THE ROLE OF CHANCE: We observed that decidua basalis was significantly stiffer than decidua parietalis, at 1250 and 171 Pa, respectively (P < 0.05). The stiffness of decidua parietalis was similar to nonpregnant endometrium and placental tissue (250 and 232 Pa, respectively). These findings suggest that it is the presence of invading EVT that is driving the increase in stiffness in decidua basalis. The stiffness of Matrigel® was found to be 331 Pa, significantly lower than decidua basalis (P < 0.05). LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: Tissue stiffness was derived by ex vivo measurements on blocks of fresh tissue in the absence of blood flow. The nonpregnant endometrium samples were obtained from women undergoing treatment for infertility. These may not reflect the stiffness of endometrium from normal fertile women. WIDER IMPLICATIONS OF THE FINDINGS: These results provide direct measurements of tissue stiffness during the window of implantation and first trimester of human pregnancy. They serve as a basis of future studies exploring the impact of mechanics on embryo implantation and development of the placenta. The findings provide important baseline data to inform matrix stiffness requirements when developing in vitro models of trophoblast stem cell development and migration that more closely resemble the decidua in vivo. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Centre for Trophoblast Research, the Wellcome Trust (090108/Z/09/Z, 085992/Z/08/Z), the Medical Research Council (MR/P001092/1), the European Research Council (772426), an Engineering and Physical Sciences Research Council Doctoral Training Award (1354760), a UK Medical Research Council and Sackler Foundation Doctoral Training Grant (RG70550) and a Wellcome Trust Doctoral Studentship (215226/Z/19/Z).
CRIS-Team Scopus Importer:2020-08-12
Keywords: blastocyst implantation; human; mechanics; tissue stiffness; trophoblast invasion

Towards brain-tissue-like biomaterials - Axpe, Eneko; Orive, Gorka; Franze, Kristian; Appel, Eric A. (Nature Communications, 2020)
CRIS-Team Scopus Importer:2020-08-12

Unrestrained growth of correctly oriented microtubules instructs axonal microtubule orientation - Jakobs, Maximilian A.H.; Zemel, Assaf; Franze, Kristian (eLife, 2022)
In many eukaryotic cells, directed molecular transport occurs along microtubules. Within neuronal axons, transport over vast distances particularly relies on uniformly oriented microtubules, whose plus-ends point towards the distal axon tip (anterogradely polymerizing, or plus-end-out). However, axonal microtubules initially have mixed orientations, and how they orient during development is not yet fully understood. Using live imaging of primary Drosophila melanogaster neurons, we found that, in the distal part of the axon, catastrophe rates of plus-end-out microtubules were significantly reduced compared to those of minus-end-out microtubules. Physical modelling revealed that plus-end-out microtubules should therefore exhibit persistent long-term growth, while growth of minus-end-out microtubules should be limited, leading to a bias in overall axonal microtubule orientation. Using chemical and physical perturbations of microtubule growth and genetic perturbations of the anti -catastrophe factor p150, which was enriched in the distal axon tip, we confirmed that the enhanced growth of plus-end-out microtubules is critical for achieving uniform microtubule orientation. Computer simulations of axon development integrating the enhanced plus-end-out microtubule growth identified here with previously suggested mechanisms, that is, dynein-based microtubule sliding and augmin-mediated templating, correctly predicted the long-term evolution of axonal microtubule orientation as found in our experiments. Our study thus leads to a holistic explanation of how axonal microtubules orient uniformly, a prerequisite for efficient long-range transport essential for neuronal functioning.
CRIS-Team Scopus Importer:2022-10-21
Keywords: axons; D. melanogaster; microtubule orientation; microtubule polarity; neurons; physics of living systems

Vinculin is required for neuronal mechanosensing but not for axon outgrowth - Wang, De-Yao; Melero, Cristina; Albaraky, Ashwaq; Atherton, Paul; Jansen, Karin A.; Dimitracopoulos, Andrea; Dajas-Bailador, Federico; Reid, Adam; Franze, Kristian; Ballestrem, Christoph (Experimental Cell Research, 2021)
Integrin receptors are transmembrane proteins that bind to the extracellular matrix (ECM). In most animal cell types integrins cluster together with adaptor proteins at focal adhesions that sense and respond to external mechanical signals. In the central nervous system (CNS), ECM proteins are sparsely distributed, the tissue is comparatively soft and neurons do not form focal adhesions. Thus, how neurons sense tissue stiffness is currently poorly understood. Here, we found that integrins and the integrin-associated proteins talin and focal adhesion kinase (FAK) are required for the outgrowth of neuronal processes. Vinculin, however, whilst not required for neurite outgrowth was a key regulator of integrin-mediated mechanosensing of neurons. During growth, growth cones of axons of CNS derived cells exerted dynamic stresses of around 10–12 Pa on their environment, and axons grew significantly longer on soft (0.4 kPa) compared to stiff (8 kPa) substrates. Depletion of vinculin blocked this ability of growth cones to distinguish between soft and stiff substrates. These data suggest that vinculin in neurons acts as a key mechanosensor, involved in the regulation of growth cone motility.
CRIS-Team Scopus Importer:2021-09-17